Impact of Intellectual Capital, Firm Performance, Firm Size, and Intangible Assets on Firm Value: Evidence from LQ45 Companies - Prasasti, Eka; Fadah, Isti; Paramu, Hadi (LifeSciFi, 2025)
This research explores the impact of Intellectual Capital (IC), Firm Performance, Firm Size, and Intangible Assets on Firm Value, while also assessing differences in IC's effect between firms with varying IC intensity. Additionally, it analyzes changes in Firm Value across the pandemic and post-pandemic periods. The study utilizes a sample of 45 firms included in the LQ45 Index, covering the period from February 1 to July 31, 2024. Data analysis employs multiple linear regression and the Difference-in-Differences (DiD) method using SPSS 26. The findings indicate that while IC, Firm Performance, Firm Size, and Intangible Assets collectively influence Firm Value, only Firm Performance, Firm Size, and Intangible Assets exhibit significant partial effects. Furthermore, no significant difference is found in IC's impact between firms with high and low IC intensity. The study also shows that the pandemic period does not significantly alter Firm Value determinants, suggesting firms have successfully adapted to changing economic conditions.